BCS coupling in a 1D Luttinger liquid - R Eneias; A Ferraz (New Journal of Physics, 2015)
In this work we investigate the effect produced by the BCS coupling in spinless fermions in one spatial dimension. Using bosonization techniques our initial model is rewritten in terms of a sine-Gordon field and a free massless scalar field. As a result the Cooper pair in our scenario is made up of soliton and antisoliton particles. We calculate the single particle Green’s function, the pair correlation function and the optical conductivity associated with the physical fermions and we show how they differ from their conventional quasiparticle analogues. Finally, we compare our results with related experimental findings for high temperature superconductors and we display how they fit qualitatively well the related observed effects produced by the anti-nodal quasiparticles in those materials.